Teacher educators' professional identity formation in a challenging context : experience from Eritrea - Isotalo, Sara (2017)
In Eritrea, the education sector is currently under reform pursuing to equip the teacher education to meet the country’s critical need for sufficiently qualified teachers. Here, teacher educators have a critical role in defining the quality of teacher education. Earlier research suggests that examining the implications of teacher educators’ professional identity formation for their professional development is crucial in developing the quality of future teachers. Yet, little is known of the identities and practices of teacher educators in Eritrea. This study thus focuses on examining the relationship between the teacher educators’ professional identities and their allegedly challenging working environment, and further factors that affect their identity formation. The research data was collected at the College of Education in Eritrea by interviewing 10 local teacher educators. The data was further analyzed by using a qualitative content analysis.